2022
DOI: 10.1038/s41598-022-04789-9
|View full text |Cite
|
Sign up to set email alerts
|

Higher trait neuroticism is associated with greater fatty acid amide hydrolase binding in borderline and antisocial personality disorders

Abstract: Borderline personality disorder (BPD) and antisocial personality disorder (ASPD) are the two most frequently diagnosed and researched DSM-5 personality disorders, and both are characterized by high levels of trait neuroticism. Fatty acid amide hydrolase (FAAH), an enzyme of the endocannabinoid system (ECS), has been linked to regulation of mood through modulation of anandamide, an endocannabinoid. We hypothesized that prefrontal cortex (PFC) FAAH binding would relate to trait neuroticism in personality disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 73 publications
0
3
0
1
Order By: Relevance
“…Intriguingly, the only patient that did not report any benefit (participant #5) was treated with a chemotype 2 oral extract alone, which seems in agreement with the hypothesis that either fast-acting administration of inhaled THC or prolonged accumulation of oral CBD in higher doses may be a more effective strategy to help EUPD patients cope with their symptoms. This is based upon recent clinical studies which demonstrated an association between elevated FAAH activity in key brain regions, such as the prefrontal cortex, and impulsivity/neuroticism seen in EUPD and other personality disorders, such as personality disorder by using functional imaging techniques, such as 11 C-CURB positron emission tomography (PET) [ 40 ]. Circulating levels of AEA appear to be reduced in EUPD patients, potentially due to the observed exacerbated FAAH expression in key neural circuits, which may, in turn, result in a deficient local endocannabinoid tone in key neural circuits ( Figure 1 B).…”
Section: Resultsmentioning
confidence: 99%
“…Intriguingly, the only patient that did not report any benefit (participant #5) was treated with a chemotype 2 oral extract alone, which seems in agreement with the hypothesis that either fast-acting administration of inhaled THC or prolonged accumulation of oral CBD in higher doses may be a more effective strategy to help EUPD patients cope with their symptoms. This is based upon recent clinical studies which demonstrated an association between elevated FAAH activity in key brain regions, such as the prefrontal cortex, and impulsivity/neuroticism seen in EUPD and other personality disorders, such as personality disorder by using functional imaging techniques, such as 11 C-CURB positron emission tomography (PET) [ 40 ]. Circulating levels of AEA appear to be reduced in EUPD patients, potentially due to the observed exacerbated FAAH expression in key neural circuits, which may, in turn, result in a deficient local endocannabinoid tone in key neural circuits ( Figure 1 B).…”
Section: Resultsmentioning
confidence: 99%
“…Research on the ECS might also benefit from a symptom domain specific approach. Instead of studying BPD and ASPD as unitary concepts, different dimensions of these disorders could be investigated, such as aggression (Kolla & Mishra, 2018), impulsivity (Lafenêtre et al., 2009), neuroticism (Juhasz et al., 2009; Kolla et al., 2022), and hostility (Wei et al., 2017). This framework might be more clinically relevant, as the assessment of pathological personality traits may be more predictive of interpersonal problems that contribute to the individual seeking treatment (Fowler et al., 2015), and one neurotransmitter system alone is unlikely to explain all the symptoms of BPD or ASPD.…”
Section: Discussionmentioning
confidence: 99%
“…Research on the ECS might also benefit from a symptom domain specific approach. Instead of studying BPD and ASPD as unitary concepts, different dimensions of these disorders could be investigated, such as aggression (Kolla & Mishra, 2018), impulsivity (Lafenêtre et al, 2009), neuroticism (Juhasz et al, 2009;Kolla et al, 2022), and hostility (Wei et al, 2017).…”
Section: Future Directionsmentioning
confidence: 99%
“…The general population varies markedly in this trait, which is of profound public health importance. Amide hydrolase is an enzyme linked to mood regulation through modulation of the endocannabinoid lipid mediator anandamide or arachidonoylethanolamide [47].…”
Section: Aetiological Role Of the Endocannabinoid Systemmentioning
confidence: 99%